The Effectiveness of Poster Vs Video in Speaking Skill of EFL Learners - Yavani, Zakky; Anani, Nur (Universitas Islam Negeri Raden Intan Lampung, 2018)
EFL Learners’ difficulties in speaking are complex. Often times, the problems are on what to speak which leads the EFL learners hesitate and become not confidence when speaking. This study aims to know the effectiveness of poster and video in assisting students when speaking. Using quasi experimental method by setting X AK2 class as an experimental (using poster) and PM2 class as control group (using video), Independent sample t-test was used to test the hyphothesis in this study. the finding shows that using poster significantly gives affects more on students’ speaking performance. This conclusion is based on the significance value calculation of 0.000 which is smaller than 0.05. while, t-count (4.870) is higher than t-table (1.994). Therefore, the hypothesis of this study is accepted. It means that the using poster significantly improves the students’ speaking ability in the English teaching.